The effect of physical therapy intervention on pain and functional in pre-operative lumbar spinal stenosis (LSS) patients - Yuningsih, Dwi; Setiawan, Danur (Journal Physical Therapy UNISA, 2022)
Lumbar Spinal Stenosis (LSS) is the focal narrowing of the spinal canal. Nerve root canal or intervertebral foramina which many elderly suffer from, is characterized by pain, disability, risk of falling and depression. The incidence of LSS is estimated to increase along with the increase in the number of the elderly population. Patients with LSS symptoms are more effective at getting operative with the installation of a specific inplant or by decompression surgery with or without fusion than conservative intervention that continue to be performed whenever three to six months of conservative measures fail. Because the gradually slow progression of the disease naturally and the complications of the surgical procedure, it is recommended that conservative management such as physiotherapy intervention be performed before surgical intervention. The purpose of this study was to determine the effect of manual therapy and exercise on pain scores and functional abilities of patients with LSS before receiving surgery. The research method is quantitatively experimental. The research sample amounted to 30 people taken with a non-random sampling technique from a spine clinic patient at the Orthopedic Orthopedic Hospital Prof. Dr. R. Soeharso Surakarta. The effect of physiotherapy intervention on pain was measured by a visual analoge scale (VAS) and functional ability was measured with the Oswestry Disability Index (ODI). results are analyzed by t-test. The results of this study showed the influence of manual therapy and exercise statistically significant on pain (p = 0.000) and functional ability (p = 0.000). In the questions of each session, there was an influence on: pain intensity, lifting activity, sitting and no effect of physiotherapy actions on self-care sessions, walking, standing, sleeping, sexual activity, social life and traveling/traveling. Manual therapy and exercises affect the reduction of pain and the improvement of the functional ability of LSS patients.